(untitled) (Anclajes, 2018)
During the last years, the affective dimension has become a novel approach towards the analyses of memory experiences linked to the Argentinian process of violence and political radicalization in the seventies. From this perspective, we intend to analyze the text Who do you think you are? by Ángela Urondo Raboy. We inquire about the idea of a “love experience”, built on certain discussions in the context of the affective turn and contemporary social theory, oriented to question the affective dimension from a non-romantic viewpoint. Furthermore, we intend to understand the relationship between this experience and the construction of the “missing parents´ daughter” identity, focusing on the overlapping of different registers presented in the text. Finally, we problematize the particular interpretation of the revolutionary militancy during the seventies, considering the way in which the author approaches to the understanding of the relationship between militant subjectivities and political-military organizations.